Enrobing Ceremony for Municipal Court Judge R. L. "Chip" Putnam in Jury Assembly Room - Watkins, Howard::::::::: (1987)
Judge John "Nip" Gallagher congratulating Judge Putnam; wife, Carol Putnam holding judicial robe; En Banc court in background